Gender Verses and Women's Resilience in Education and Socio-Culture: Mubadalah Faqihuddin Abdul Kodir's Perspective - Emilia Angraini; Abdul Kahar (STAI Syaichona Moh. Cholil Bangkalan, 2024)
One of the topics that is frequently discussed is gender, particularly when it comes to Qur'anic interpretation. This study explores the issue of gender justice in the Qur'an with the perspective of reading Mubadala, especially related to verses often interpreted as gender bias and the form of women's resilience to the injustice that occurs. This study is a library research study with a qualitative approach; the data sources of this study consist of primary and secondary data sources. In comparison, the data collection technique used is documentation with the descriptive analysis method. The results of this study indicate that the method of reading Mubadala has a positive contribution to the role of women, and the form of women's resilience in dealing with gender injustice is carried out through three efforts: education, courage to speak up, and self-management.